Formation of a dense cloud of points and its processing when creating a digital model of the terrain - Butenko, Ye.; Kutsenko, O.; Tertyshna, О.; Tkachuk, Ye.; Yaretska, K. (Land Management, Cadastre and Land Monitoring, 2024)
The article explores the creation of digital terrain models (DRMs) based on dense point cloud classification in QGIS, Digitals, and 3D Survey software.In the research process, a dense cloud of points created during 3D scanning of the territory of the botanical garden of NUBiP of Ukraine was used, followed by classification and construction of digital relief models in various software tools.The stages of point cloud classification, creation of classification layers, data export to QGIS, Digitals and 3D Survey software tools for further modeling and drawing of models with isolines were studied.The digital model of the relief and the stages of its creation, "cleaning" of the original cloud of points of different density are considered.On the basis of the same initial data, a dense cloud of points, the formation of digital models of the relief of the territory of the botanical garden of NUBiP of Ukraine was carried out in various software tools.The process of creating a digital relief model was investigated based on a dense point cloud using QGIS, Digitals, 3D Survey programs.The main advantages and disadvantages of building a digital relief model based on a cloud of points formed by the results of 3D scanning are analyzed.Features and capabilities of software tools QGIS, Digitals, 3D Survey and their ability to build 3D surfaces based on exported point clouds are considered.Keywords: digital terrain model, QGIS, digital survey, 3D survey, 3D model, 3D scan, 3D Survey, QGIS, Digitals, point cloud, isoline, construction of horizons.
Keywords: digital terrain model; digital survey; 3D model; 3D scan; 3D Survey; QGIS; Digitals point cloud; isoline; construction of horizons